The Influence Of Organizational Culture, Work Environment And Job Satisfaction On Organizational Commitment In Educational Foundations - Mujitahid; Andi NU Graha; Dianawati Suryaningtyas (Indonesian Journal Publisher, 2026)
Organizational commitment and the factors that influence it have been widely discussed in previous studies, but there are still few studies that examine the influence of organizational culture, work environment and job satisfaction simultaneously on organizational commitment in foundations. The purpose of this study is to analyze the influence of organizational culture, work environment and satisfaction on organizational commitment. The type of research used in this study is quantitative research. The study was conducted at the Al Muwahidin Lelede Foundation. The target in this study were all permanent employees of the Al Muwahidin Lelede Foundation. The population was all permanent employees of the Al Muwahidin Lelede Foundation, which amounted to 81 employees. Organizational culture, work environment, and job satisfaction have a significant influence on organizational commitment, because organizational commitment is formed by indicators of affective commitment, continuance commitment and normative commitment, it turns out that the dominant results are in the affective commitment indicator. It is recommended to improve organizational commitment factors, attention needs to be paid 3 to normative commitment by having responsibility to help the organization achieve its goals. To improve organizational culture, attention needs to be paid to maintaining and maintaining work stability with the foundation having the ability to adapt to change, but still maintaining work stability.